2013
DOI: 10.1093/icvts/ivt229
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged intensive care treatment of octogenarians after cardiac surgery: a reasonable economic burden?†

Abstract: Presented data propose that advanced age is correlated with a higher mortality, but not with prolonged ICU treatment or higher costs after cardiac surgery. Considering the encouraging functional status and QOL of the survivors, the financial burden caused by octogenarians is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…The other 7 studies 3,7,9,27,28,33,34 showed similar results, with QOL considerably reduced in the prolonged ICU group, particularly in domains reflecting physical activity. In 8 of 9 studies demonstrating a deterioration in QOL, there was a higher early and late mortality.…”
Section: Studies Showing No Improvement/negative Impact On Qolmentioning
confidence: 67%
See 4 more Smart Citations
“…The other 7 studies 3,7,9,27,28,33,34 showed similar results, with QOL considerably reduced in the prolonged ICU group, particularly in domains reflecting physical activity. In 8 of 9 studies demonstrating a deterioration in QOL, there was a higher early and late mortality.…”
Section: Studies Showing No Improvement/negative Impact On Qolmentioning
confidence: 67%
“…The other 16 studies were retrospective (Table 3). 3,7,9,[25][26][27][28][29][30][31][32][33][34][35][36][37] The retrospective studies included 1,438 patients. Two studies were prospective and included 100 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations